2018
DOI: 10.1590/1807-57622017.0184
|View full text |Cite
|
Sign up to set email alerts
|

Construção da identidade profissional na Educação Interprofissional em Saúde: percepção de egressos

Abstract: This is an exploratory, descriptive-analytical study, qualitative and longitudinal in nature. It presents the perception of graduates about the construction of professional identity from the perspective of Interprofessional Education, with data collected in interviews with graduates of the program from six health professions. The results were organized into guiding nuclei and processed using content analysis. The results are presented as regards the nucleus Interprofessional Education and the construction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
54

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 20 publications
0
8
0
54
Order By: Relevance
“…The results showed the development of essential competencies for health professions: problem solving, decision making, leadership, mutual trust and respect, communication with patients and other professionals, understanding the problems' nature, understanding clinical cases under the patient's perspective. Among graduate students, 84% are happy with the education they received and provided contributions for health education analysis under the interprofessional education's perspective 32 .…”
Section: Experience Analysis: Research Viewsmentioning
confidence: 99%
“…The results showed the development of essential competencies for health professions: problem solving, decision making, leadership, mutual trust and respect, communication with patients and other professionals, understanding the problems' nature, understanding clinical cases under the patient's perspective. Among graduate students, 84% are happy with the education they received and provided contributions for health education analysis under the interprofessional education's perspective 32 .…”
Section: Experience Analysis: Research Viewsmentioning
confidence: 99%
“…This process plays a critical role in the construction of capacities for an effective collaboration among professionals. Rossit et al 53 have confirmed this idea in a study with graduates from courses with a multiprofessional approach, highlighting that the recognition of the singularity of different professions strengthens professional identity in collaborative work.…”
Section: Achievements and New Challenges In Interprofessional Educationmentioning
confidence: 83%
“…Obviamente, nos módulos oferecidos pelos eixos comuns, há menos autonomia para mudanças, pois há que se encontrar um mínimo denominador que atenda a todos os cursos. Essa restrição, no entanto, é compensada pela experiência relevante da educação interprofissional, verificada tanto no estudo bibliográfico quanto nas pesquisas realizadas no campus 20 . Com relação à flexibilização curricular, nota-se, no Gráfico 2, a existência de uma carga horária (160 horas) destinada aos módulos eletivos, sendo que os estudantes poderão optar por cursá-los em outros campi ou em outros cursos, além dos ofertados pelos próprios professores do curso que aprofundam determinadas temáticas não contempladas na matriz curricular; por exemplo, "Juventudes: vulnerabilidades e marcadores sociais da diferença"; "Saúde mental infantil", "Biomecânica", "Fundamentos biológicos do adoecimento humano"; etc.…”
Section: Resultado Da Revisãounclassified